The Requirement of Forming Words and Involving Attitudes in Naming Products: The Skincare of Wardah - Mulia, Vilya Lakstian Catra; Annaningtyas, Cucut; May Cahyani Putri (Institut Agama Islam Negeri Palopo, 2024)
Beauty industry is a challenging business globally. Besides its promotion and expansion, product naming reflects its uniqueness. Through this research, the analysis shows how word contributes in product naming and the track of negotiation to the customers. By conducting morphology and crosschecked by appraisal in Systemic Functional Linguistics (SFL) studies, The researcher analyses word formation and attitude towards the categories and products of Wardah Skincare. Studying the one of Indonesian fast-growing beauty industry, this research is done by qualitative paradigm. The analysis is done in word level by criterion-based sampling to apply in four stages of analysis technique consisting domain, taxonomy, componential, and cultural theme. The researcher found that word formation process is frequently practiced in naming skincare product informing physical, composition, and function aspects. However, it does not result attitude at the same time. Its existence supports the product through the words conveying benefit, opportunity, specialization, and innovation. The more products are offered; word formation is done to create heterogeneous options. On the other hand, attitude reflects sensation, visual emphasis, protection, and capacity.